Analisa Pengaruh Ketersediaan Fasilitas, Kualitas dan Efektivitas Pelayanan Terhadap Kepuasan Pasien di Poli Umum Klinik Medika POLRES Semarang - Nur Ghaliyah Sandra Putri; Sarah Mareta Devira; Gusti Ayu Kade Devina Muryantisa; Innocentius Bernarto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted to examine and provide an analysis of the availability of facilities, quality of service, and their effectiveness in relation to patient satisfaction at the General Outpatient Clinic of Medika Clinic, Semarang Police Department. This research employs a quantitative approach with a descriptive method. Data were collected through questionnaires completed by respondents, with samples obtained using an accidental sampling technique. This sampling method involves selecting individuals who happened to be present at the location during the time the research was conducted.